Pertanggung Jawaban Pidana Korporasi Terhadap Tindak Pidana Usaha Penyediaan Listrik Tanpa Izin - Prakasa, Ragil Surya; Azzahra, Dinda; Mutia, Putri; Fauzi, Gamawan; Olivia, Putri Yaldi; Putra, Rizki Eka (eScience Humanity Journal, 2024)
The Republic of Indonesia is a country that is actively developing in various sectors. Several forms and developments in various sectors can be seen now, such as the economic, technological and social sectors and so on. All business entities, both legal entities and non-legal entities, are called corporations. Corporations are subjects of criminal acts. Meanwhile, to be held criminally accountable, a physical form is required. Crimes committed by corporations are very detrimental to society and the state. This study uses a normative legal research type. The data obtained in this study were then analyzed qualitatively, the Descriptive Analysis Method is a research method. Based on the research results, the legal provisions for criminal acts of providing electricity without an operating permit according to Law 30 of 2009 concerning Electricity are regulated in Article 49 paragraph (2) which states that: "Any person who carries out the business of providing electricity without an operating permit as referred to in Article 22 shall be punished with a maximum imprisonment of 5 years and a maximum fine of IDR 4,000,000,000 (four billion rupiah)".